Territory Management Based On The Assessment Of Environmental Noise In Near Areas To Two Medical Centers Of Zone Planning Units 44 And 47 In Bogotá - Acevedo Buitrago, Baudilio; Ortíz Bernal, Deisy Mireya; Ramírez Trujillo , Estefanía (Ingeniería Solidaria, 2020)
Introduction:This article shows the evaluation of environmental noise around the medical centers located in the UPZ Americas and Kennedy Central - Bogotá, and the proposal of some actions related to the planning of the territory as a strategy for mitigation. Problem:The Kennedy town has presented high levels of environmental noise, which is a worrying aspect due to its correlation with the effects on people’s health. Objective:This research was conducted for the purpose of compiling updated information on environmental noise in the Kennedy locality and evaluating regulatory compliance and identifing the phenomena to establish actions that lead to its mitigation. Methodology:The measurement process was guided under the guidelines of ISO 1996:1 and the parameters established in Res. 627/2006 of the Ministry of Environment. Results:The ambient noise levels exceed the maximum permissible limits (55 dB) on the different days and hours of measurement. It was also determined that this phenomenon is mainly related to high vehicular flow as well as formal and informal commercial activities around medical centers. Conclusion:There is no regulatory compliance in relation to environmental noise and the territorial plan established in the UPZ. The suggested actions are: use of parks to plant native trees that act as biological barriers, non-use of surrounding streets as secondary traffic roads and reorganization of trade activities. Originality:Updated environmental noise data was obtained around medical centers in Kennedy and problems of inappropriate growth and development were identified. Limitations:Lack of information on environmental noise measurements in other sectors of the area.